A method for preparing a hard shed for composite crossarms

By blending bisphenol A type epoxy resin and dimer acid modified epoxy resin, a hard umbrella skirt was prepared, which solved the problems of low mechanical strength and poor aging resistance of existing composite insulated umbrella skirt materials, and achieved higher mechanical strength and better aging resistance.

CN116003968BActive Publication Date: 2025-04-25HAINAN POWER GRID CO LTD ELECTRIC POWER RES INST
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310006336.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-04
Publication Date
2025-04-25
Estimated Expiration
2043-01-04

AI Technical Summary

Technical Problem

The existing composite insulated cross-skirt material has low mechanical strength and rapidly aging in humid and heat and salt spray environments, resulting in a reduced service life.

Method used

Blends of bisphenol A type epoxy resin and dimer acid modified epoxy resin (EPD-172) are used to prepare a hard umbrella skirt through specific mixing ratios and process flow. The process includes mixing bisphenol A epoxy resin, EPD-172 epoxy resin, curing agent and accelerator, stirring through water bath, vacuum drying and vacuum defoaming treatment, and finally curing in a heated curing furnace.

Benefits of technology

The prepared hard umbrella skirt has good mechanical strength and crack resistance, can remain stable under strong wind and bird pecking conditions, and exhibits excellent aging resistance in humid and heat and salt spray aging environment, extending service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116003968B_ABST
    Figure CN116003968B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a hard shed applied to a composite crossarm. Bisphenol A epoxy resin, dimer acid-modified epoxy resin, a curing agent and an accelerator are used as raw materials to prepare a hard shed with excellent electrical and mechanical properties. The hard shed prepared by the invention is applied to the composite crossarm. According to tests, the hard shed of the invention can solve the problems of loss of the traditional composite crossarm shed caused by human trampling, bird pecking and strong wind damage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of composite insulating crossarms, and in particular to a method for preparing a hard shed applied to a composite crossarm. Background Art

[0002] The composite insulation crossarm tower is composed of a steel structure tower body and a composite insulation crossarm, and is replacing the traditional line combination of "iron crossarm + side phase insulator". The composite material of the composite insulation crossarm is one of the ideal materials for building power towers due to its advantages of light weight, high strength, corrosion resistance, easy processing, designability and good insulation performance. The composite insulation crossarm can give full play to its superior insulation performance, realize the perfect combination of functional materials and structural materials, and maximize the performance of composite materials, with significant technical advantages and application prospects.

[0003] Dimer acid modified epoxy resin is an adduct of epichlorohydrin and dibasic fatty acid, and has the characteristics of good adhesion, excellent resistance to external impact and thermal shock, good lap shear strength and creep resistance. Among them, EPD-172 dimer acid modified epoxy resin is a polymer of C18-unsaturated fatty acid dimer with 4,4'-(1-methylethylene)diphenol and chloromethyl oxirane. It is usually mixed with other epoxy resins and diluents for toughening epoxy systems in the electrical materials industry, improving adhesion and peel strength. EPD-172 epoxy resin can effectively improve the ability of cured products to withstand mechanical impact and increase the service life of electrical equipment. However, it has disadvantages such as low production and high price.

[0004] Bisphenol A epoxy resin has convenient raw material sources and low cost. It is the most widely used in epoxy resins, and its output accounts for more than 85% of the total output of epoxy resins. E-51 bisphenol A epoxy resin has excellent insulation and corrosion resistance, but its heat resistance and weather resistance are poor, and its toughness is not good. Therefore, blending EPD-172 dimer acid modified epoxy resin and E-51 bisphenol A epoxy resin can combine the advantages of both to obtain a new epoxy resin with excellent comprehensive performance.

[0005] Application number CN106567604A is a shed-type cement-based composite insulating crossarm and its preparation process, which mixes short fibers, water-based epoxy resin, silicate cement and quartz sand into a cement-based composite material, and forms a composite insulating component with a shed structure after high-temperature curing. Although the mechanical strength is improved to a certain extent, the composite material is heavy and has poor crack resistance.

[0006] The application number is CN113845757A, a corrosion-resistant high electrical performance resin and a preparation method thereof. The corrosion-resistant high electrical performance resin is composed of an epoxy resin, a curing agent and an accelerator. The epoxy resin is composed of 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexyl formate and bisphenol A epoxy resin, and the amount of the 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexyl formate accounts for 10% to 40% of the mass of the epoxy resin. With the improvement of composite material technology and production technology, silicone rubber crossarms are currently widely used in China, that is, silicone rubber sheds and sheaths are arranged on the composite material core rod, which has good pollution flashover resistance. However, in actual application, it is found that the silicone rubber insulating crossarm has the disadvantages of low mechanical strength and cannot be stepped on by humans, and the silicone rubber sheds and sheaths are seriously damaged by birds and strong winds. In view of the fact that Hainan is an island city with more humid and hot weather, it is easy to cause the sheds to age and crack, and the service life is reduced. Therefore, choosing more reasonable insulating materials and improving the shed of the composite crossarm into a hard shed with better mechanical strength can effectively improve the safety and reliability of power lines and reduce the loss of the hard shed. Summary of the invention

[0007] In view of this, the present invention proposes a method for preparing a hard shed for a composite crossarm to solve the above problems.

[0008] The technical solution of the present invention is achieved in this way:

[0009] A hard shed applied to a composite cross arm comprises bisphenol A epoxy resin and dimer acid modified epoxy resin, wherein the dimer acid modified epoxy resin is EPD-172 epoxy resin.

[0010] Furthermore, by weight, the dimer acid-modified epoxy resin comprises 9-11 parts, the bisphenol A epoxy resin comprises 88-92 parts, the curing agent comprises 68-72 parts, and the accelerator comprises 0.49-0.53 parts.

[0011] Furthermore, the bisphenol A epoxy resin is E-51 bisphenol A epoxy resin, the curing agent is 2-methylhexahydrophthalic anhydride, and the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol.

[0012] Further, it is characterized by comprising the following steps:

[0013] (1) adding bisphenol A epoxy resin and dimer acid modified epoxy resin into a container and mixing them, then sequentially adding a curing agent and an accelerator, and mixing them in a water bath to prepare a resin glue solution;

[0014] (2) placing the resin glue solution in a vacuum drying oven for treatment to obtain an epoxy resin glue material;

[0015] (3) Pour the epoxy resin into the mold, perform vacuum degassing, solidify, cool, and demould to obtain the finished product.

[0016] Furthermore, in step (1), the temperature of the water bath is 55-65° C., and the mixture is stirred in the water bath for 6-8 minutes.

[0017] Furthermore, in step (2), the temperature of the vacuum drying oven is 55-65° C., and the drying time is 13-17 min.

[0018] Furthermore, in step (3), the vacuum degassing treatment temperature is 55-65° C., and the drying time is 13-17 min.

[0019] Furthermore, in step (3), the curing temperature is 130-150° C., and the curing time is 9-11 hours.

[0020] Furthermore, the preparation method of the composite insulating crossarm with hard shed is as follows: first, connecting the two ends of the insulating core rod to hardware, and obtaining the insulating core rod and hardware composite by crimping; second, preheating the insulating core rod and hardware composite and placing them in a mold, closing the mold, and then injecting the vacuum-stirred mixed epoxy resin adhesive until the adhesive entering the mold is filled; finally, placing the mold and the product together in a heating and curing furnace for curing, curing the mixed epoxy resin adhesive serving as the outer insulating shed, and obtaining the composite insulating crossarm with hard shed after curing.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention prepares a hard shed for composite insulating crossarms, which is composed of bisphenol A epoxy resin and dimer acid modified epoxy resin, and the specific dimer acid modified epoxy resin is EPD-172 epoxy resin. The hard shed prepared by the present invention has the advantages of lightness, good crack resistance, etc., and its electrical and mechanical properties are improved. After mechanical property testing, the results show that the hard shed prepared by the present invention has excellent mechanical properties and can meet the application in strong wind climates and strong bird pecking conditions. After the moisture and heat resistance and salt spray aging tests, after 96 hours of moisture and heat aging and 21 days of salt spray aging, the leakage current after 96 hours of moisture and heat aging is 37.60μA, the breakdown field strength is 36.68kV / mm, the bending strength is 16.88MPa, and the tensile strength is 61.15MPa; after 21 days of salt spray aging, the leakage current is 36.35μA, the breakdown field strength is 38.6kV / mm, the bending strength is 22.56MPa, and the tensile strength is 60.42MPa. The results show that the hard shed prepared by the present invention has excellent aging resistance, can adapt to local weather, and prolong the service life of the hard shed. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a schematic diagram of the composite cross arm of the present invention, comprising a hard shed 2, a hard sheath 3, a core rod and a hardware 1. The hard sheath is wrapped around the outside of the core rod, and a plurality of hard sheds are arranged on the outer surface of the hard sheath. The sheds are hard sheds prepared by the present invention. The hardware is arranged at both ends of the core rod, and the core rod is located in the center hole of the hardware. DETAILED DESCRIPTION

[0024] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.

[0025] Example 1

[0026] Step 1, weigh 90 parts of E-51 resin and 10 parts of dimer acid modified epoxy resin EPD-172 resin by weight, add them into a container, weigh 70 parts of curing agent 2-methylhexahydrophthalic anhydride, add them into the container, and finally add 0.51 parts of accelerator (DMP-30);

[0027] Step 2, maintaining a constant temperature of 60° C. in a water bath and stirring for 7 minutes to obtain a resin glue solution;

[0028] Step 3, performing vacuum degassing treatment in a vacuum drying oven at a temperature of 60° C. for 15 minutes to obtain a vacuum-stirred epoxy resin adhesive;

[0029] Step 4, slowly pour the mixed solution into a preheated stainless steel mold coated with a release agent, and then perform a constant temperature vacuum degassing treatment for 15 minutes;

[0030] Step 5, curing at a temperature of 140° C. for 10 h, naturally cooling, and demoulding to obtain an EPD-172 / E-51 blended resin cured product, and testing the relevant properties of the hard shed material.

[0031] The preparation method of the composite insulating crossarm with hard sheds comprises the following steps: firstly, connecting the two ends of an insulating core rod with hardware fittings, and obtaining an insulating core rod and hardware fitting composite body by crimping; secondly, preheating the insulating core rod and hardware fitting composite body and placing them into a mold, closing the mold, and then injecting vacuum-stirred mixed epoxy resin adhesive until the adhesive entering the mold is fully filled; finally, placing the mold together with the product into a heating and curing furnace for curing, curing the mixed epoxy resin adhesive as the outer insulating shed, and obtaining the composite insulating crossarm with the hard shed after curing.

[0032] Example 2

[0033] Step 1, by weight, weigh 88 parts of E-51 resin and 9 parts of dimer acid modified epoxy resin EPD-172 resin, add them to a container, weigh 68 parts of curing agent 2-methylhexahydrophthalic anhydride, add them to the container, and finally add 0.49 parts of accelerator (DMP-30);

[0034] Step 2, maintaining a constant temperature of 55° C. in a water bath and stirring for 6 minutes to obtain a resin glue solution;

[0035] Step 3, performing vacuum degassing treatment in a vacuum drying oven at a temperature of 55° C. for 15 minutes to obtain a vacuum-stirred epoxy resin adhesive;

[0036] Step 4, slowly pouring the mixed solution into a preheated stainless steel mold coated with a release agent, and then performing a constant temperature vacuum degassing treatment for 15 minutes, wherein the temperature is 55° C.;

[0037] Step 5, curing at a temperature of 130° C. for 9 hours, natural cooling, and demoulding to obtain an EPD-172 / E-51 blended resin cured product, and testing the relevant properties of the hard shed material.

[0038] The preparation method of the composite insulating crossarm with hard shed skirt comprises the following steps: firstly, connecting the two ends of the insulating core rod with hardware fittings, and obtaining the insulating core rod and hardware fitting composite body by crimping; secondly, preheating the insulating core rod and hardware fitting composite body and placing them into a mold, closing the mold, and then injecting the mixed epoxy resin adhesive material stirred in vacuum until the adhesive material entering the mold is filled; finally, placing the mold together with the product into a heating curing furnace for curing, curing the mixed epoxy resin adhesive material as the outer insulating shed skirt, and obtaining the composite insulating crossarm with hard shed skirt after curing.

[0039] Example 3

[0040] Step 1, by weight, weigh 92 parts of E-51 resin and 11 parts of dimer acid modified epoxy resin EPD-172 resin, add them to a container, then weigh 72 parts of curing agent 2-methylhexahydrophthalic anhydride, add them to the container, and finally add 0.53 parts of accelerator (DMP-30);

[0041] Step 2, maintaining a constant temperature of 65° C. in a water bath and stirring for 8 minutes to obtain a resin glue solution;

[0042] Step 3, performing vacuum degassing treatment in a vacuum drying oven at a temperature of 65° C. for 15 minutes to obtain a vacuum-stirred epoxy resin compound;

[0043] Step 4, slowly pour the mixed solution into a preheated stainless steel mold coated with a release agent, and then perform a constant temperature vacuum degassing treatment for 15 minutes at a temperature of 65°C;

[0044] Step 5, curing at a temperature of 150° C. for 11 hours, natural cooling, and demoulding to obtain an EPD-172 / E-51 blended resin cured product, and testing the relevant properties of the hard shed material.

[0045] The preparation method of the composite insulating crossarm with hard sheds comprises the following steps: firstly, connecting the two ends of an insulating core rod with hardware fittings, and obtaining an insulating core rod and hardware fitting composite body by crimping; secondly, preheating the insulating core rod and hardware fitting composite body and placing them into a mold, closing the mold, and then injecting vacuum-stirred mixed epoxy resin adhesive until the adhesive entering the mold is fully filled; finally, placing the mold together with the product into a heating and curing furnace for curing, curing the mixed epoxy resin adhesive as the outer insulating shed, and obtaining the composite insulating crossarm with the hard shed after curing.

[0046] Test Example 1

[0047] The following method is used to detect the performance of the hard shed prepared in Example 1.

[0048] 1. Test of aging resistance: The prepared hard shed samples were subjected to artificial accelerated aging test in a deionized water bath at 85℃. The sampling period was 4d, 8d, 12d, and 16d. The mechanical and electrical properties of the shed samples were measured before and after aging.

[0049] 2. Salt spray aging resistance test: The hard shed samples were subjected to aging test according to GB / T 2423.17-2008. Neutral salt spray conditions were used, and the test solution was an aqueous solution of analytical pure NaCl with a mass fraction of 5%. The samples were kept in a constant temperature environment of 35°C and the relative humidity at the nozzle was at least 85%. The sampling period was 4d, 7d, 14d, and 28d. After sampling, the sample surface was cleaned with deionized water to remove the influence of the mist liquid. The mechanical properties and electrical properties of the shed samples before and after aging were measured.

[0050] 3. Mechanical properties test: The hard shed samples prepared were tested according to standard ISO527-2. The dumbbell-shaped tensile sample cut by engraving machine had a middle width of 10mm, a gauge length of 50mm, and a test rate of 5mm / min. In the bending test, the rectangular sample cut by engraving machine according to standard IS178 had a size of 80×15×4mm, a span of 64mm, and a test rate of 2mm / min.

[0051] 4. Leakage current test: The prepared hard shed samples were tested according to standard DL / T 1580-2016. The sample length was 300mm±0.5mm, and the leakage current value was measured with an oscilloscope under power frequency 12kV voltage.

[0052] 5. Power frequency breakdown test: Test the prepared hard shed samples according to standard IEC 60243-1-2013. Place a square test piece with a side length of 150mm and a thickness of 1mm in a transparent glass container filled with dimethyl silicone oil, ensuring that the silicone oil covers the sample by 5-7mm. Select 3 test pieces for each group of samples, and take 5 breakdown test points for each test piece.

[0053] 6. Dielectric loss test: Use a dielectric loss meter to test the dielectric loss factor of the test sample at 50Hz at room temperature. The dielectric loss sample is a circular thin sheet sample with a side length of 30mm and a thickness of 3mm.

[0054] The bending strength and tensile strength of the hard shed prepared in Example 1 of the present invention are 23.01 MPa and 82.72 MPa respectively. The experimental results show that the hard shed has excellent mechanical properties and can meet the application requirements in strong wind climates and strong bird pecking conditions.

[0055] The rigid shed obtained in Example 1 of the present invention has a leakage current of 35.42μA before aging, a breakdown field strength of 43.8kV / mm, a bending strength of 23.01MPa, and a tensile strength of 82.72MPa. After 96h of wet heat aging and 21d of salt spray aging, the leakage current of 96h of wet heat aging is 37.60μA, the breakdown field strength is 36.68kV / mm, the bending strength is 16.88MPa, and the tensile strength is 61.15MPa; the leakage current of 21d of salt spray aging is 36.35μA, the breakdown field strength is 38.6kV / mm, the bending strength is 22.56MPa, and the tensile strength is 60.42MPa. The experimental results show that the rigid shed obtained in the present invention has good resistance to wet heat aging and salt spray resistance, can adapt to the weather in Hainan Province, and reduce material loss caused by environmental factors.

[0056] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A hard shed applied to a composite cross arm, characterized in that: It includes bisphenol A epoxy resin and dimer acid modified epoxy resin, wherein the dimer acid modified epoxy resin is EPD-172 epoxy resin, and the raw materials include 9-11 parts of dimer acid modified epoxy resin, 88-92 parts of bisphenol A epoxy resin, 68-72 parts of curing agent, and 0.49-0.53 parts of accelerator in parts by weight; The bisphenol A epoxy resin is E-51 bisphenol A epoxy resin, the accelerator is 2, 4, 6-tris(dimethylaminomethyl)phenol, and the curing agent is 2-methylhexahydrophthalic anhydride.

2. The method for preparing a hard shed for a composite crossarm according to claim 1, characterized in that: The following steps are involved: (1) adding bisphenol A epoxy resin and dimer acid modified epoxy resin into a container and mixing them, then adding curing agent and accelerator in sequence, and mixing them in a water bath to prepare a resin glue solution; (2) placing the resin glue liquid in a vacuum drying oven for treatment to obtain an epoxy resin glue compound; (3) Pour the epoxy resin into the mold, perform vacuum degassing, solidify, cool, and demould to obtain the finished product.

3. The method for preparing a hard shed for a composite crossarm according to claim 2, characterized in that: In step (1), the temperature of the water bath is 55-65° C., and the mixture is stirred in the water bath for 6-8 minutes.

4. The method for preparing a hard shed for a composite crossarm according to claim 2, characterized in that: In step (2), the temperature of the vacuum drying oven is 55-65°C, and the drying time is 13-17 minutes.

5. The method for preparing a hard shed for a composite crossarm according to claim 2, characterized in that: In step (3), the vacuum degassing treatment temperature is 55-65°C, and the drying time is 13-17 minutes.

6. The method for preparing a hard shed for a composite crossarm according to claim 2, characterized in that: In step (3), the curing temperature is 130-150° C. and the curing time is 9-11 hours.

Citation Information

Patent Citations

  • Umbrella skirt type cement-based composite insulated cross arm and manufacturing technology thereof

    CN106567604A

  • Corrosion-resistant resin with high electrical performance and preparation method thereof

    CN113845757A

  • Preparation method of dimer acid modified epoxy resin toughened carbon fiber prepreg

    CN103113716A

  • Outdoor electric-insulation modified epoxy resin composition

    CN104177780A

  • Combined type bird pecking preventing composite insulator

    CN106971798A